2021
DOI: 10.1111/ipd.12781
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported knowledge, attitudes, and practice of final‐year dental students in relation to child abuse: A multi‐centre study

Abstract: Background:The number of child abuse cases is increasing worldwide; therefore, it is important to educate individuals having contact with children about it. This includes dentists who play a pivotal role in detecting and reporting child abuse. Aim: To identify and compare the final-year dental student's knowledge, attitudes, and practice in relation to child abuse. Design: A 38-item and four-part online questionnaire was distributed to students of 11 dental schools in 10 countries. SPSS and GraphPad Prism were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In our study, we found insufficient knowledge regarding CAN among dental graduates in Saudi Arabia. This is in agreement with the study conducted by Duman et al, in which they assessed knowledge regarding CAN among undergraduate students from 11 dental schools across the world [ 20 ]. Their study showed that dental students from Australia, Pakistan, Turkey, Jordan, Turkish Republic of Northern Cyprus, Poland, the Republic of South Africa, Nigeria, Cambodia, and the United States of America lack knowledge and experience in recognizing and reporting child abuse.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found insufficient knowledge regarding CAN among dental graduates in Saudi Arabia. This is in agreement with the study conducted by Duman et al, in which they assessed knowledge regarding CAN among undergraduate students from 11 dental schools across the world [ 20 ]. Their study showed that dental students from Australia, Pakistan, Turkey, Jordan, Turkish Republic of Northern Cyprus, Poland, the Republic of South Africa, Nigeria, Cambodia, and the United States of America lack knowledge and experience in recognizing and reporting child abuse.…”
Section: Discussionsupporting
confidence: 92%
“…Continuing this issue, a study coordinated by Duman et al (2021) assessed knowledge of child abuse in dentistry students from 11 colleges around the world, covering continents such as Africa, Asia, North America, Europe and Oceania. The results revealed significant gaps in students' knowledge regarding the recognition of mistreatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies included in this systematic review, there were differences in relation to the undergraduate period in which the students were. The studies conducted by Sousa et al [37] and Duman et al [50] evaluated only final-year students, but other studies evaluated students from the first graduation level [30,38,43,47]. This point can lead to differences in the perception and knowledge related to their ability to identify and approach these patients.…”
Section: Discussionmentioning
confidence: 99%